2019
DOI: 10.26508/lsa.201900425
|View full text |Cite
|
Sign up to set email alerts
|

Stromal fibroblasts induce metastatic tumor cell clusters via epithelial–mesenchymal plasticity

Abstract: Emerging evidence supports the hypothesis that multicellular tumor clusters invade and seed metastasis. However, whether tumor-associated stroma induces epithelial–mesenchymal plasticity in tumor cell clusters, to promote invasion and metastasis, remains unknown. We demonstrate herein that carcinoma-associated fibroblasts (CAFs) frequently present in tumor stroma drive the formation of tumor cell clusters composed of two distinct cancer cell populations, one in a highly epithelial (E-cadherinhiZEB1lo/neg: Ehi)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 69 publications
2
71
0
Order By: Relevance
“…1c), consistent with a previous report indicating partial EMT induced in the breast, head and neck cancer cells to be associated with the tumor stroma. 27,54 However, ZEB1 staining was also detected in tumor cells that are not adjacent to the stroma in some PDXs (P10, P21 and P38) with abundant ZEB1 expression ( Fig. 1d).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…1c), consistent with a previous report indicating partial EMT induced in the breast, head and neck cancer cells to be associated with the tumor stroma. 27,54 However, ZEB1 staining was also detected in tumor cells that are not adjacent to the stroma in some PDXs (P10, P21 and P38) with abundant ZEB1 expression ( Fig. 1d).…”
Section: Discussionmentioning
confidence: 96%
“…However, roles of EMT in the tumor cell clusters involved in metastasis formation remain unknown. Studies focusing on collective cancer cell migration have also depended mostly on specific cultured cell lines and experimental murine tumors, while investigations using human clinical materials are rare . The cellular and molecular mechanisms, by which tumor cell clusters invade and seed metastases via EMT, also have not as yet been sufficiently examined using human materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santi et al suggested that cancer and stromal cells of invasive tumors may have been in direct contact and may have established complex crosstalk during tumor development [98]. CAFs induce the formation of metastasizing clusters of tumor cells, with the participation of an intercellular adhesion [103]. According to the authors, CAFs may drive the formation of tumor cell clusters composed of two distinct cancer cell populations, one in a highly epithelial state and another in a hybrid epithelial/mesenchymal state and confer invasive and metastatic traits upon tumor cells.…”
Section: Circulating Cancer Cells Form Clusters Through Tomo-and Hetementioning
confidence: 99%
“…Besides, CAFs may be involved in tumor cell cluster formation by promoting in a paracrine fashion the invasion of groups of cancer cells, through the induction of EMP. A recent work in breast cancer shows that CAF-released SDF-1 and TGF-β drive the formation and maintenance of a hybrid population of epithelial/mesenchymal (E/M) cells and highly epithelial (E) cells within clusters of cancer cells [ 134 ]. E/M cells are induced by the expression of ZEB1 and lead the collective migration, while E cells, acting as follower cells, preserve cell-cell adhesions that enable cluster formation and show a higher metastatic seeding ability in mouse models [ 134 ].…”
Section: Role Of Cafs In Ctc Cluster Formationmentioning
confidence: 99%